PENGENALAN PERPUSTAKAAN DIGITAL UNTUK MENDUKUNG GERAKAN LITERASI NASIONAL - Elly Astuti; Triana Triana; Riki Yulianto (Gapenas Publisher, 2021)
This community development activity aims to introduce digital libraries that various regions have developed to support the national literacy movement. The condition of the COVID-19 pandemic that requires online learning is one of our most important reasons to provide insight into the availability of complete and practical reading resources. The devotion results showed that participants were very enthusiastic about getting to know this application. The majority of participants revealed that the existence of this library is interesting and practical because it can read exciting books according to the interests of talent anywhere and anytime.